2021
DOI: 10.1002/arch.21831
|View full text |Cite
|
Sign up to set email alerts
|

Expression stability of candidate RT‐qPCR housekeeping genes in Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: Reverse‐transcription quantitative polymerase chain reaction (RT‐qPCR) is commonly used to quantify gene expression. For normalization, the expression of each gene is compared with a reference “housekeeping” gene that is stably expressed under relevant stress. Unfortunately, there have been no reports on the stability of such reference genes under various treatments of the Spodoptera frugiperda. In this study, we used five tools (RefFinder, GeNorm, NormFinder, BestKeeper, and ΔCt methods) to evaluate the stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Teng et al 75 reported elongation factor2 ( eEF2 ) as the most stably expressed gene in different developmental stages of Plutella xylostella . The expression stability of eEF2 in developmental stages and tissues was also documented in Agrilus planipennis 76 ; I. sexdentatus 43 ; Sogatella furcifera 77 ; Mythimna separata 63 , 78 ; Tuta absoluta 61 ; Hippodamia variegate 42 ; Spodoptera frugiperda 64 . However, Ponton et al 32 reported that the elongation factor was unsuitable for normalization of relative expression due to the different expression variability in different experimental conditions in Drosophila melanogaster .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Teng et al 75 reported elongation factor2 ( eEF2 ) as the most stably expressed gene in different developmental stages of Plutella xylostella . The expression stability of eEF2 in developmental stages and tissues was also documented in Agrilus planipennis 76 ; I. sexdentatus 43 ; Sogatella furcifera 77 ; Mythimna separata 63 , 78 ; Tuta absoluta 61 ; Hippodamia variegate 42 ; Spodoptera frugiperda 64 . However, Ponton et al 32 reported that the elongation factor was unsuitable for normalization of relative expression due to the different expression variability in different experimental conditions in Drosophila melanogaster .…”
Section: Discussionmentioning
confidence: 78%
“…RPS13 and RPS7 exhibited the most stable expression under larval-crowding conditions in Mythimna separata 63 . Similarly, different developmental stages ( RPL32, RPS18 ) and different tissues ( RPS18 ) of Spodoptera frugiperda showed the most stable expression 64 , whereas RPS26 and RPL32 genes showed the same in Thermobia domestica 65 ; RPS11 , RPL28 , and RPL10 genes showed Tuta absoluta 58 ; RPS18 and RPL13 genes showed Rhopalosiphum padi tissues 66 . Sellamuthu et al 43 reported that RPS3 is stably expressed in the developmental stage, sex-specific and tissue-specific conditions in pine-feeding bark beetle, I. sexdentatus .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The primer for GAPDH (GenBank accession No. OK319027.1) was designed using NCBI primer 3 tools, and primers for other candidate genes were described by Zhou et al (2021). The cycle threshold (Ct) of each gene was obtained by quantitative Real-Time PCR (qRT-PCR) using TranStart® Top Green qPCR SuperMix (+ Dye II).…”
Section: Stability Analysis Of Reference Genes For Quantitative Real-...mentioning
confidence: 99%
“…Consideration of the significance and diverse specificity of reference genes, many reference gene sets have been validated in various insect species, such as Spodoptera frugiperda ( Zhou et al, 2021 ), Rhopalosiphum padi ( Li M. et al, 2021 ), Aquatica leii ( Fu and Meyer-Rochow, 2021 ), Tuta absoluta ( Yan et al, 2021 ), Dichelops melacanthus ( Pinheiro et al, 2020 ), Thermobia domestica ( Bai et al, 2020 ), Apolygus lucorum ( Luo et al, 2020 ), Lymantria dispar ( Yin et al, 2020 ), Drosophila melanogaster ( Kim et al, 2020 ), Phenacoccus solenopsis ( Zheng et al, 2019 ), Chilo partellus ( Adeyinka et al, 2019 ), Harmonia axyridis ( Yang et al, 2018 ), Liriomyza trifolii ( Chang et al, 2017 ), Myzus persicae ( Kang et al, 2017 ), and B. odoriphaga ( Shi et al, 2016 ) under various experimental conditions. However, a universal reference gene has not yet been identified.…”
Section: Introductionmentioning
confidence: 99%